Możliwości budowania i utrzymania relacji w społeczności wirtualnej studentów jako odbiorców medialnych w erze Web 2.0 - Sudewicz, Karol; Nazaruk, Stanisława (Kultura-Społeczeństwo-Edukacja, 2025)
In the modern world, it is difficult to imagine life without the Internet and even without an account on a chosen social networking site. Observing various types of activities on the Internet and the rapid pace of changes occurring there, the need for conducting a research was noticed, in which the key question was formulated: is it possible to build lasting relationships in a virtual community? The research was conducted among students of various fields of study in a group of 236 people. A diagnostic survey method and an author’s survey questionnaire were used, due to the fact that no standardized measurement tools have been found for the stated research problem to date. The research was conducted online, which made it easier to reach respondents from different regions of Poland. According to the surveyed students, it is possible to build relationships in the virtual world but they are less lasting than those established in the real world. However, it is difficult to determine whether virtual relationships can develop into friendships. Students are aware of what can destroy interpersonal relationships.